The Use of TikTok Social Media @TRAC_Astra as a Creative Promotion Platform - Arifah, Engelberg Nur; Dharmawan, Leonard (CV. Rayyan Dwi Bharata, 2026)
Digital transformation encourages companies to develop innovative communication strategies through social media. TRAC Astra, a transportation service provider under PT Serasi Autoraya, utilizes its TikTok account @trac_astra as a creative promotional platform to strengthen brand identity and reach a wider audience. The creative content strategy implemented consists of several stages, including trend research, storyboard development, and idea approval through Notion.In the production stage, the creative team highlights corporate values such as professionalism and comfort through visual elements and talent selection. Meanwhile, in the post-production stage, the consistent use of blue, white, and orange is applied to maintain strong brand identity.The form of creativity is analyzed using Kapferer’s Brand Identity Prism theory, which consists of six dimensions. The physical dimension is reflected through consistent logo placement and color palette; personality through friendly yet professional communication style; culture through values of reliability and excellent service; relationship through interaction built with the audience; reflection through the portrayal of users as modern and confident individuals; and self-image through expressions of pride and trust toward the brand.The results of the study indicate that TRAC Astra successfully integrates creativity and brand identity, producing content that not only attracts audience attention but also strengthens emotional connection and brand loyalty.